An investigation into the influential factors that impact consumer decision-making among prospective online MBA students. Issue 2 (3rd July 2022) - Jeckells, Harriet
ABSTRACT: This research investigates the influential factors impacting CDM among prospective online MBA students, using qualitative interviews. This research focus is contextualised with analysis on the CDM process and the disparity between UK and international students, to gain a deeper understanding of the dynamics of the influential factors. The findings of this research point to accreditation, price and rankings having the most influence on CDM among prospective online MBA students. It suggests that the CDM process among international students is more extensive than among UK students. International students' searches had a longer duration, compared more programme alternatives, favoured detailed information such as course content and marketing materials, and searches often culminated in an application to more than one university. Meanwhile, UK students were more influenced by outbound university phone communications, which the data imply is attributable to English being their first language. Concluding practical recommendations include marketing messaging optimisation, strategic focus on rankings, accreditation and pricing and driving brand loyalty among prospective international students.